L’usage des exemples dans l’enseignement de la physique à l’université : un marqueur de l’identité pédagogique des enseignants-chercheurs ? - Cécile de Hosson; Nicolas Décamp; Philippe Colin (Recherches en Éducation)
Using examples in physics teaching at university level is commonplace and inevitable. As researchers in physics education (didactic of physics) we question what academics in physics say when they describe why, when and how they use examples while they teach. These declared uses are considered as markers of the relationships academics maintain with the teaching and the learning of the physics; they allow us to go back to certain dimensions of their professional identity, considered in its epistemological and educational dimensions.